1986
DOI: 10.1007/bf00903352
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glicentin-related peptides on glucagon secretion in anaesthetized dogs

Abstract: Recent studies have demonstrated that glicentin is released during nutrient ingestion. However, the biological function of glicentin remains unclear. In order to clarify the role of glicentin in the enteroinsular axis, the effect of glicentin-related peptides was investigated using in vivo local circulation of canine pancreas. Peaks I and II of gut glucagon-like immunoreactivity, partially purified from porcine intestinal extract by affinity chromatography and gel filtration, synthesized hexadecapeptide of N-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…Furthermore, the C-terminal portion of glicentin (glicentin 62-69) induced an increase in insulin secretion and a decrease in glucagon secretion. The present study thus confirmed partly the results obtained in the previous study (Ohneda et al 1986). In addition, glucagon administered at the end of each experiment induced an increase in plasma insulin and at the same time a reasonable rise of plasma glucagon concentration in the pancreaticoduodenal vein.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Furthermore, the C-terminal portion of glicentin (glicentin 62-69) induced an increase in insulin secretion and a decrease in glucagon secretion. The present study thus confirmed partly the results obtained in the previous study (Ohneda et al 1986). In addition, glucagon administered at the end of each experiment induced an increase in plasma insulin and at the same time a reasonable rise of plasma glucagon concentration in the pancreaticoduodenal vein.…”
Section: Discussionsupporting
confidence: 93%
“…According to the previous study (Ohneda et al 1986), both glicentin 1-16 and glicentin 62-69 induced a slight inhibition of glucagon secretion in the basal state. In the present study, in oiler to elucidate the effect of glicentin-related peptides upon the endocrine function of the pancreas much more definitely, four peptides were infused into the pancreaticoduodenal artery during arginine infusion.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations